‘It Touched My Heart’ - Trust and Attachment in the Aftermath of Trauma for Cambodian Orphans and Young People (European Journal of Behavioral Sciences, 2022)
The last two decades have seen significant economic advancements in Cambodia. However, high poverty levels remain, particularly in rural communities. Poverty, in conjunction with work scarcity, often leads to the disruption of the nuclear family as parents may have to migrate to find work. As a result, children are often the most vulnerable in a landscape of broken families, many living with grandparents or are placed in residential care facilities as “orphans”, despite having living parents. This article stems from a broader body of doctoral research in the area of trauma and resilience. This research project interviewed 40 participants, incorporating a resilience scale and timeline alongside a qualitative interview technique. The focus of this article underscores attachment and social connectedness in the recovery from trauma for 26 young people (aged 18-30) that were interviewed for this study. This article presents some of the key findings that capture the voices of young Cambodian trauma survivors (many of whom are orphans) who have lived experiences of broken families, jails and institutions, residential and/or foster care. The findings of this study demonstrate the importance that healthy relational interactions and attachment in buffering the impact of childhood trauma.